2002
DOI: 10.3928/0022-0124-20020901-05
|View full text |Cite
|
Sign up to set email alerts
|

New Graduate Orientation in the Rural Community Hospital

Abstract: Retention rates for 1-year new graduate nurses had fallen to 30% at the author's institution. Upon reviewing feedback, a lack of a new graduate orientation program was determined to be a significant factor. The challenge presented to staff development was to develop a program that would increase 1-year retention rates of new graduate nurses without incurring overtime costs or significant additional expenses. The result was a successful 8-week orientation program using multiple teaching methods. New graduates r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 7 publications
0
32
0
1
Order By: Relevance
“…The studies were conducted in the United Kingdom (UK) (n = 2), USA (n = 24), Australia (n = 2), New Zealand (n = 1) and Thailand (n = 1). Sample sizes ranged from 9 (Squires, 2002) to 6000 (Ulrich et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The studies were conducted in the United Kingdom (UK) (n = 2), USA (n = 24), Australia (n = 2), New Zealand (n = 1) and Thailand (n = 1). Sample sizes ranged from 9 (Squires, 2002) to 6000 (Ulrich et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…O'Malley Floyd et al, 2005 showed that 77% (24/31) participants envisaged themselves becoming more knowledgeable and confident as measured using a yes/no questionnaire reply. Similarly, Squires (2002) found that respondents reported an overall perception of 'increased confidence'; however this was not statistically significant due to a very small sample size (n = 9).…”
Section: Confidence Competence and Knowledgementioning
confidence: 90%
See 3 more Smart Citations